Flexibility and Work-Life Interference in Australia - Pocock, B; Skinner, N (My University, 2011)
This contribution examines the relationship between flexibility and work—life interference. It analyses requests for flexibility in Australia just prior to the enactment of a new ‘right to request’ such flexibility, utilizing a large employee survey that shows that around a fifth of employees requested flexibility, most requests were agreed, and work—life outcomes were much better amongst those whose requests were fully agreed. Women were twice as likely as men to have sought flexibility, with one in two mothers of preschoolers, one in three mothers of children under 16 and a quarter of women without children having made requests. Parenting made no difference to men’s rate of request-making. Findings suggest that the right may be particularly beneficial to the third of all workers who have not made requests for flexibility yet are not content with current arrangements. There is a case to extend the right beyond parents, and for stronger appeal rights.
Keywords: Employment; Labour market; Employment; Employment and unemployment